Mitigasi Risiko Dalam Transaksi E-Commerce : Keseimbangan Perlindungan Hukum antara Konsumen dan Pelaku Usaha - Sani, Anita; Emirzon, Joni; Yahanan, Annalisa (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2024)
In e-commerce transactions, there is often an imbalance between consumers and business actors. Most people's perception is that consumers in e-commerce are in a weak bargaining position. Consumers are felt to be the object of activity to reap maximum profits (profit oriented) by business actors. Consumers are still vulnerable to rights violations and are always at a disadvantage. However, in e-commerce transactions, business actors are sometimes faced with a weak position. However, the fact is that in online transactions, losses can not only be experienced by consumers but also by business actors. Losses experienced by business actors are caused by the failure to fulfill the achievements that should be fulfilled by consumers. Even though both parties have not yet fulfilled their achievements, the business actor has processed the goods ordered by consumers using his personal money. For this reason, mitigation efforts need to be made to create a balanced position between consumers and business actors.